Association between maternal smoking during pregnancy and smoking behaviors in adult offspring - Yang, Lin; Li, Jing; Chen, Yinzi; Wei, Yanling; Song, Congying; Zhang, Jingwen; Dai, Liang; Shi, Yu; Xiong, Zuying; Shan, Ying; Huang, Xiaoyan (Frontiers in Public Health, 2025)
BackgroundMaternal smoking during pregnancy (MSP) is associated with offspring smoking. However, there is still scant evidence to support the association between MSP and smoking behaviors in adult offspring.MethodsThis is a prospective cohort study based on the UK Biobank. Maternal smoking around birth was reported by the offspring through a questionnaire. Participants with unknown maternal smoking status were classified as having missing values. Logistic regression, linear regression and negative binomial regression models were used to estimate the associations of exposure to maternal smoking around birth with four outcomes of offspring smoking behaviors, including smoking status, age started smoking, pack years of smoking, and number of unsuccessful stop-smoking attempts.ResultsWe included 156,604, 101,204, 96,466, and 70,308 participants in the analyses of smoking status, age started smoking, pack years of smoking, and number of unsuccessful stop-smoking attempts, respectively. After adjusted for potential confounders, MSP demonstrated significant associations with offspring smoking (OR: 1.08 [95% CI: 1.07, 1.10]), age started smoking (beta per year: −0.83 [95% CI: −0.89, −0.77]), pack years of smoking (beta per pack-year: 3.51 [95% CI: 3.28, 3.74]) and number of unsuccessful stop-smoking attempts (IRR: 1.11 [95% CI 1.09, 1.13]). Subgroup analysis showed the excessive risks for smoking status and age started smoking in females, pack years of smoking in males, and for number of unsuccessful stop-smoking attempts in the non-breastfeeding group.ConclusionThe unfavorable effects of maternal smoking around birth might reach at least up to offspring’s middle even older age. Smoking cessation before pregnancy should be encouraged to prevent the transmission to the next generation.